The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7cc02747h
|View full text |Cite
|
Sign up to set email alerts
|

An example of unusual pyridine donor Schiff base uranyl (UO22+) complexes

Abstract: The pentadentate coordination environment of a 2,6-bis[1-[(2-hydroxyphenyl)imino]ethyl] pyridine ligand scaffold was designed to accommodate the larger atomic radius of uranium as the uranyl dioxo cation, while fully occupying its equatorial plane. Here, two new uranyl (UO) complexes utilizing this scaffold have been synthesized from successive condensation reactions and subsequent metal complexation. Surprising Zn fluorescence is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
4
10
0
Order By: Relevance
“…29,30,47 In unit A (Figure 5), the quinoid-type distortions of the rings can be seen, though they are subtle, especially in comparison to that of 19) Å, which is much more consistent with a reduced bond order than with a typical double bond. The equatorial U−N and U−O bond lengths of 2.558( 12) and 2.319( 10) are consistent with the assignment of a U(VI) species 18,48 and suggest the nitrogen is still donating as a neutral atom, not an anionic one, which would be reflected by U−N distances approximately 0.20 Å shorter than those observed. 16 In solution, this species shows no indication of persistent radicals, as the NMR spectra appear typical for diamagnetic complexes, and is EPR silent.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…29,30,47 In unit A (Figure 5), the quinoid-type distortions of the rings can be seen, though they are subtle, especially in comparison to that of 19) Å, which is much more consistent with a reduced bond order than with a typical double bond. The equatorial U−N and U−O bond lengths of 2.558( 12) and 2.319( 10) are consistent with the assignment of a U(VI) species 18,48 and suggest the nitrogen is still donating as a neutral atom, not an anionic one, which would be reflected by U−N distances approximately 0.20 Å shorter than those observed. 16 In solution, this species shows no indication of persistent radicals, as the NMR spectra appear typical for diamagnetic complexes, and is EPR silent.…”
Section: ■ Results and Discussionsupporting
confidence: 78%
“…Despite the esd values being large, this difference is still meaningful as it coincides with some elongation of the average C–N distance to 1.281(19) Å, which is intermediate to the approximately 1.32 Å distance diagnostic of the singly reduced radical anion form and the approximately 1.24 Å distance for neutral gbha species. , Interestingly, unit A, which has a very intermediate C7–C8 distance of 1.44(2) Å, has a longer average C–N distance of 1.311(19) Å, which is much more consistent with a reduced bond order than with a typical double bond. The equatorial U–N and U–O bond lengths of 2.558(12) and 2.319(10) are consistent with the assignment of a U­(VI) species , and suggest the nitrogen is still donating as a neutral atom, not an anionic one, which would be reflected by U–N distances approximately 0.20 Å shorter than those observed . In solution, this species shows no indication of persistent radicals, as the NMR spectra appear typical for diamagnetic complexes, and is EPR silent.…”
Section: Resultssupporting
confidence: 70%
“…Fluorescence spectra of the three complexes showed maximum emission around 415 nm. napthyl, 42) [232]. The Schiff base ligands fully occupy the equatorial plane with the less strongly coordinating pyridine occupying the fifth site of the pentagon.…”
Section: Pentadentate Schiff Base Cd(ii) Complexesmentioning
confidence: 99%
“…In this regard, the fundamental science of actinides is becoming more and more important. However, diverse species, abundant oxidation states (OS), and easy coordination with various ancillary ligands almost throughout all elements in the periodic table make the actinide chemistry rather complicated. , Among them, thermodynamically stable and kinetically inert hexavalent uranyl U VI O 2 2+ is the most prevalent form of uranium, representing 98% in the spent nuclear fuel and having an environmental implication. Recent studies have found that the uranyl­(VI) is able to interact with other actinyl or actinide to construct cation–cation interaction (CCIs) complexes in solution and solid state, although CCIs are well recognized between pentavalent actinyl ions An V O 2 + (An = U, Np, and Pu). …”
Section: Introductionmentioning
confidence: 99%